Fruit and seed diversity of introduced Phoenix dactylifera in Yuanjiang of Yunnan Province - DING Bing; LI Lianfang; WANG Kanglin; WANG Wenjun; YANG Liying; WU Chengpeng (Xibei zhiwu xuebao)
[Objective] Analysis of diversity of fruit and seed traits (FSTs) of 32 P . dactylifera plants introduced in Yuanjiang, Yunnan Province was carried out, and the excellent single plant in the population was preliminarily identified, which provided the basis for further research and breeding of improved varieties. [Methods] 11 parameters of 32 P . dactylifera plants were measured. The methods of Shannon- Wiener index and principal component analysis etc. were employed to interpret the diversity of FSTs, and primarily to determine the excellent individual plants in the population. [Results] The mean transverse and longitudinal diameters (TD and LD) of fruits, single fruit dry weight (SFDM), and fruit edible rates (FER) of the 32 P . dactylifera plants were 1.9-2.7 cm, 2.9-4.2 cm, 1.9-5.6 g, and 77.8%- 94.9%, respectively; the coefficient of variation (CV) for fresh seed weight (FSW) was the highest (29.9%), followed by SFDM (29.7%), with CV of FER the lowest (5.3%). SFDM was significantly positively correlated with the other parameters (P <0.05 or P <0.01). The FER was significantly negatively correlated with fruit moisture content, TD and LD of seed, seed fresh weight, and seed moisture content (P <0.01). A comprehensive score of ≥1.000 was identified as the breeding standard for improved varieties, with 5 plants selected from 32 individual plants, which accounting for 15.6% of the total plants. [Conclusion] The fruit and seed variety of the single plant of P . dactylifera is rich, and the proportion of excellent single plant in the population is low, so the breeding of good varieties is important to increase its yield and value.